Sustainability standards and certification: looking through the lens of Foucault's dispositif. (24th August 2016) - SILVA‐CASTAÑEDA, LAURA; TRUSSART, NATHALIE
Abstract: Over the past few decades, sustainability standards and certification have come to play an important role in the global governance of production and trade. Their purpose is to address the environmental and social problems generated by the globalization of the economy. Yet, as scholars and actors alike have pointed out, framing these problems in terms of technical criteria and procedures might result in rendering some issues invisible and closing potential debate and contestation. Through the empirical analysis of a multi‐stakeholder initiative called the 'Roundtable of Sustainable Palm Oil', our aim is to explore how civil society organizations and advocacy networks nevertheless draw new lines of power by using, putting to the test, correcting and constructing formalized knowledge. To shed light on these processes of resistance, we advance an analytic that restores the concept of dispositif coined by Michel Foucault in emphasizing both the disruptive and stabilizing lines that compose a dispositif .